Laju Deoksigenasi Dan Laju Reaerasi Sungai Bedadung Segmen Desa Gumelar Kabupaten Jember - Sri Wahyuningsih; Elida Novita; Rizky Fathonah Imami (agriTECH, 2019)
Bedadung River is the main river in the Bedadung Watershed in Jember Regency. People use the river to fulfill their daily needs and agricultural irrigation. Organic pollutants from domestic wastewater and agriculture wastewater that enter in river can decrease dissolved oxygen concentration, which can influence the river’s water quality. The river has a self-purification system with a reaeration and deoxygenation mechanism. The purpose of this study was to analyze the rate of deoxygenation and reaeration using the Streeter-Phelps method. Deoxygenation and reaeration rates influence oxygen concentration. This research took water samples using a Grab Sampling technique as the primary data at 5 nodes and 4 segmentations. The results of the research showed that the deoxygenation rate was 0.036 mg/L.day and the reaeration rate was 0.046 mg/L.day. This meant that the deoxygenation rate was lower than the reaeration rate so the self-purification can run quite well. The average DO value was 7.62 mg/L, showed that the river according to the class III water quality standard, so, the water quality was good and save to be used by the public. The research result can be used to determine the water quality carrying capacity in the next research.